For a philosophical history of Behaviorism - Lopes, Carlos Eduardo; Laurenti, Carolina (Perspectivas em Análise do Comportamento, 2023)
In his essay “What is Behaviorism?” Abib argues that the history of Behaviorism begins with Skinner, not with Watson. This article aims to examine that bold thesis. We start presenting Abib’s intertextual method of analysis based on philosophical and cultural scrutiny of the psychological text. Based on that method, Abib reveals the epistemological and metaphysical commitments of behavior theories by J. B. Watson, E. C. Tolman, and B. F. Skinner. From this philosophical perspective, Abib shows that only Skinner’s theory can realize the original meaning of behaviorist psychology, i.e. explaining psychological phenomena in behavior considered in its own right. We highlighted some advantages of Abib’s philosophical history over other versions of the history of Behaviorism. We finish arguing that Abib’s archaeological analysis provides useful heuristic tools to help us debate contemporary behavioral proposals.